Instantiation of crystal plasticity simulations for micromechanical modelling with direct input from microstructural data collected at light sources. (15th April 2017) - Pokharel, Reeju; Lebensohn, Ricardo A.
Abstract: Novel non-destructive characterization techniques performed at light sources provide previously inaccessible 3-D mesoscopic information on the deformation of polycrystalline materials. One major difficulty for interpretation of these experiments through micromechanical modelling is the likelihood that processing and/or mounting the sample introduce residual stresses in the specimen. These stresses need to be incorporated into crystal plasticity formulations, for these models to operate directly from microstructural images and be predictive. To achieve this, the initial micromechanical state of each voxel needs to be specified. In this letter we present a method for incorporating grain-averaged residual stresses for instantiation of crystal plasticity simulations. Graphical abstract: